A study of the effect of dietary fiber fractions obtained from artichoke (Cynara cardunculus L. var. scolymus) on the growth of intestinal bacteria associated with health. Issue 5 (13th May 2015) - Fissore, Eliana N.; Santo Domingo, Cinthia; Gerschenson, Lía N.; Giannuzzi, Leda
<x xml:space="preserve">Abstract</x> The effect of different fractions enriched in soluble fiber obtained from artichoke using citric acid or citric acid/hemicellulase on the selective growth of Lactobacillus plantarum 8114 and Bifidobacterium bifidum ATCC 11863 was evaluated.